1987
DOI: 10.1128/iai.55.6.1533-1535.1987
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Shiga toxin for primary cultures of human colonic and ileal epithelial cells

Abstract: Shiga toxin purified from Shigella dysenteriae 1 was cytotoxic to cultured epithelial cells from human colon and ileum. The cytotoxicity, which affected only about 50% of treated cells, was neutralized by rabbit antiserum monospecific for Shiga toxin and mediated by protein synthesis inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Histopathological studies of tissue samples from loops infected with SC502, the Inv-Tox+ mutant, revealed an important inflammatory infiltrate in the lamina propria and major alterations predominantly at the tips of shortened villi. These results confirmed the cytotoxicity of Shiga toxin for enterocytes in vivo (27). However, the most striking feature was infiltration of the epithelial lining of erythrocytes which were shed into the lumen along with large amounts of mucus.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Histopathological studies of tissue samples from loops infected with SC502, the Inv-Tox+ mutant, revealed an important inflammatory infiltrate in the lamina propria and major alterations predominantly at the tips of shortened villi. These results confirmed the cytotoxicity of Shiga toxin for enterocytes in vivo (27). However, the most striking feature was infiltration of the epithelial lining of erythrocytes which were shed into the lumen along with large amounts of mucus.…”
Section: Discussionsupporting
confidence: 77%
“…However, none of the experiments which have been carried out have compared isogenic mutants in a relevant cell assay system. Recent evidence indicates that Shiga toxin is cytotoxic for primary cultures of human colonic cells (27). Tissue invasion requires additional chro-mosomally encoded products, among which smooth lipopolysaccharide (43,57), a product of the Kcp locus (8,43), and aerobactin (24, 28) have been implicated.…”
mentioning
confidence: 99%
“…Analysis of the relative titre of LPS-specific faecal s-IgA revealed an increase and a prolonged response in the intermediate and severe disease groups even after the non-specific s-IgA level had dropped. The prolonged specific s-IgA produc- (36).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of protein synthesis. Protein synthesis was determined by measuring incorporation of [3H]L-leucine (27,29). Porcine aortic endothelial (PEC-15 [39]) and African green monkey kidney cells (Vero cells; ATCC CCL81; American Type Culture Collection, Rockville, Md.)…”
Section: Methodsmentioning
confidence: 99%
“…Monolayers from replicate plates were harvested with 0.05% trypsin-0.02% EDTA solution containing 0.04% (wt/ vol) trypan blue to determine cell death (26,27). Cell death was expressed as a percentage of that of the PBS control, and values were then adjusted so that the control value was 0%.…”
Section: Methodsmentioning
confidence: 99%